The Issue of Honorarium for Temporary Teachers from the Perspective of the Ijarah Contract and Islamic Economic Justice: A Literature Review - Siti Alfia; Tri Hidayati (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the phenomenon of low wages for contract teachers from the perspective of the ijarah contract and Islamic economic distributive justice, as well as to identify forms of structural injustice within the education system. The study employs a qualitative approach using a literature review. The data sources consist of 40 scientific articles obtained from the Google Scholar, Sinta, and DOAJ databases, focusing on the welfare of honorary teachers, remuneration, the ijarah contract, and distributive justice. Data collection was conducted through systematic literature review, while data analysis employed content analysis with a descriptive-analytical approach, following the stages of data reduction, data presentation, and drawing conclusions. The results indicate that the low ujrah for contract teachers not only impacts their economic well-being but also has the potential to affect the overall quality of education. In many cases, the practice of paying honoraria to contract teachers has not fully aligned with the principles of the ijarah contract, particularly regarding aspects of justice, wage adequacy, and the principle of taradhi. Furthermore, the distribution of welfare within the education system reveals disparities between civil servant (ASN) and non-ASN teachers, reflecting the suboptimal implementation of distributive justice. The implications of this study underscore the importance of reformulating wage policies and labor protections for honorary teachers that are fairer, more proportional, and in line with Islamic economic principles to support teachers’ welfare and improve the quality of education.